Mitochondrial Damage Mediated by miR-1 Overexpression in Cancer Stem Cells - Song Zhang; Cuilian Liu; Xiaobo Zhang (Elsevier, 2019)
It is well known that cells rely on mitochondrial respiration for survival. However, the effect of microRNAs (miRNAs) on mitochondria of cells has not been extensively explored. Our results indicated that the overexpression of a miRNA (miR-1) could destroy mitochondria of cancer stem cells. miR-1 was downregulated in melanoma stem cells (MSCs) and breast cancer stem cells (BCSCs) compared with cancer non-stem cells. However, the upregulation of miR-1 in cancer non-stem cells did not induce mitochondrial damage. miR-1 overexpression caused mitochondrial damage of cancer stem cells by directly targeting the 3' UTRs of MINOS1 (mitochondrial inner membrane organizing system 1) and GPD2 (glycerol-3-phosphate dehydrogenase 2) genes and interacting with LRPPRC (leucine-rich pentatricopeptide-repeat containing) protein, a protein localized in mitochondria. MINOS1, GPD2, and LRPPRC in mitochondria were required for mitochondrial inner membrane. The results of in vitro and in vivo assays demonstrated that miR-1 overexpression induced mitophagy of cancer stem cells. Therefore, our study contributed novel insights into the mechanism of miRNA-mediated regulation of mitochondria morphology of cancer stem cells. Keywords: miR-1, mitochondria, target gene, target protein, mitophagy